Mac OS X for Java geeks - Iverson, Will (O'Reilly, 2003)
Mac OS X for Java Geeks delivers a complete and detailed look at the Mac OS X platform, geared specifically at Java developers. Programmers using the 10.2 (Jaguar) release of Mac OS X, and the new JDK 1.4, have unprecedented new functionality available to them. Whether you are a Java newbie, working your way through Java Swing and classpath issues, or you are a Java guru, comfortable with digital media, reflection, and J2EE, this book will teach you how to get around on Mac OS X. You'll also get the latest information on how to build applications that run seamlessly, and identically, on Windows, Linux, Unix, and the Mac. The book begins by laying out the Mac OS X tool set, from the included Java Runtime Environment to third-party tools IDEs and Jakarta Ant. You'll then be brought up to speed on the advanced, Mac-specific extensions to Java, including the spelling framework, speech framework, and integration with QuickTime. In addition to clear explanations of these extensions, you'll learn how to write code that falls back to non-Mac specific code when it runs on other platforms, keeping your application portable. Once you have the fundamentals of the Mac OS X Java platform in hand, this book takes you beyond the basics. You'll learn how to get the Apache web server running, and supplement it with the Jakarta Tomcat JSP and servlet container. JSPs and servlets running on Mac OS X are covered, as is installation and connectivity to a database. Once you have your web applications up and running, you'll learn how to interface them with EJBs, as running the JBoss application server on Mac OS X is covered. Finally, the latest developments in web services, including XML-RPC and SOAP, are found within.